Hadith #108 - Sunan al-Nasa'i - Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Bakr bin 'Abdullah al-Mazni بكر بن عبد الله المزني; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Hamza bin al-Mughira bin Nashayt حمزة بن المغيرة بن نشيط; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) stayed behind, and I stayed with him. When he had relieved himself he said: ‘Do you have any water with you?’ I brought some water to him, and he washed his hands and face, then he started trying to uncover his arms, but the sleeves of his Jubbah were too tight, so he threw it over his shoulders and washed his arms and wiped over his forehead and ‘Imamah, and over his Khuff.”
Grade:

Hadith #265 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan al-Nasa'i)
It was narrated from Anas that the Messenger of Allah (ﷺ) used to (go around) all his wives and perform Ghusl once.
Grade:

Hadith #271 - Sunan al-Nasa'i - Abu Hurairah; Abu Rafi'; Bakr bin 'Abdullah al-Mazni بكر بن عبد الله المزني; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك (Sunan al-Nasa'i)
“While the Messenger of Allah (ﷺ) was in the Masjid, he said: ‘O ‘Aishah, hand me the garment.’ She said: ‘I am not praying.’ He said: ‘It is not in your hand.’ So she gave it to him.”
Grade:

Hadith #310 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“When any one of you prays, let him not spit in front of him or to his right, rather let him spit to his left or beneath his feet.” Then the Prophet (ﷺ) spat like this on his garment and rubbed it.
Grade:

Hadith #544 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
“I heard the Messenger of Allah (ﷺ) say on the Minbar: ‘Do not let the Bedouin make you change the name of your prayer; verily, it is ‘Isha’.'”
Grade:

Hadith #549 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) prayed Fajr on the day of Khaibar during the time it was still dark, when he was near the enemy. Then he attacked them and said: ‘Allahu Akbar! Khaibar is destroyed!’ Twice. ‘Then, when it descends in their courtyard, evil will be the morning for those who had been warned!'” As-Saffat 37:177
Grade:

Hadith #649 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“I used to call the Adhan for the Messenger of Allah (S.A.W) and in the first Adhan of Fajr I used to Say: ‘Hayya ‘ala al-falah, as-salatu khairun minan-nawm, as-salatu khairun minan-nawm, Allahu Akbar Allahu Akbar, la ilaha illallah (Come to prosperity, prayer is better than sleep, prayer is better than sleep, Allah is the Greatest, Allah is the Greatest, there is none worthy of worship except Allah).'”
Grade:

Hadith #728 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد (Sunan al-Nasa'i)
‘When you are praying, do not spit to the front or to your right. Spit behind you or to your left if there is no one there, otherwise do this.’ And he spat beneath his foot and rubbed it.'”
Grade:

Hadith #785 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘A man should not be led in prayer in his place of authority, and no one should sit in his place of honor except with his permission.”‘
Grade:

Hadith #814 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) used to gently pat our shoulders (to make sure the row was straight) at the time of prayer, and he would say: ‘Keep (the rows) straight; do not differ from one another lest your hearts should suffer from discord. Let those who are mature and wise stand closest to me, then those who are next to them, then those who are next to them.”‘
Grade:

Hadith #845 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“One day the Messenger of Allah (ﷺ) prayed Fajr, then he said: ‘Did so-and-so attend the prayer? They said: ‘No.’ He said: ‘(What about) so-and-so? They said:’No’ He said: ‘These two prayers. are the most burdensome for the hypocrites. If they knew what (virtue) there is in them, they would come, even if they had to crawl. And the virtue of the first row is like that of the row of the angels. If you knew its virtue, you would compete for it. A man’s prayer with another man is
Grade:

Hadith #901 - Sunan al-Nasa'i - Anas ibn Malik; Hajjaj bin al-Minhal حجاج بن المنهال; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan al-Nasa'i)
When the Prophet (ﷺ) started to pray he would say: “Subhanakallahumma, wa bihamdika tabarakasmuka wa ta’ala jadduka wa la ilaha ghairuk (Glory and praise be to You, O Allah. Blessed be Your name and exalted be Your majesty, there is none worthy of worship except You.)”
Grade:

Hadith #941 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
The Messenger of Allah (ﷺ) was by a pond belonging to Banu Ghifar when Jibril, peace be upon him, came to him and said: “Allah commands you to teach your Ummah the Quran with one way of recitation.” He said: “I ask my Lord for protection and forgiveness, my Ummah cannot bear that.” Then he came to him a second time and said: “Allah commands you to teach your Ummah the Quran with two ways of recitation.” He said: “”I ask my Lord for protection and forgiveness, my Ummah cannot be
Grade:

Hadith #985 - Sunan al-Nasa'i - Abdul 'Aziz bin 'Abdullah al-Majashun عبد العزيز بن عبد الله الماجشون; Amr bin Mnswr al-Nsa'iy عمرو بن منصور النسائي أبو سعيد; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Musa bin Da'ud al-Dby موسى بن داود الضبي أبو عبد الله; Umm Fadl Lubaba bint al-Harith (Sunan al-Nasa'i)
“I have never prayed behind anyone whose prayer more closely resembled that of the Messenger of Allah (ﷺ) than so-and-so. We prayed behind that person and he used to make the first two rak’ahs of Zuhr lengthy and the last two shorter, and he would make ‘Asr shorter; in Maghrib he would recite the short Mufassal surahs. In Isha’ he recited: ‘By the sun and its brightness and similar surahs, and in subh he recited two lengthy surahs.”
Grade:

Hadith #1527 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
The Prophet (ﷺ) went out and prayed for rain, then he prayed two rak’ahs in which he recited loudly.
Grade:

Hadith #1556 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
The Messenger of Allah (ﷺ) led the people in offering the fear prayer, two rak’ahs. Then he said the taslim and led others in offering the fear prayer, then he said the taslim. So the Prophet (ﷺ) had prayed four rak’ahs.
Grade:

Hadith #1580 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“I attended the prayer with the Messenger of Allah (ﷺ) on the day of ‘Eid. He started with the prayer before the Khutbah, with no Adhan and no Iqamah. When he finished the prayer, he stood leaning on Bilal, and he praised and glorified Allah (SWT) and exhorted the people, reminding them and urging them to obey Allah (SWT). Then he moved away and went to the women, and Bilal was with him. He commanded them to fear Allah (SWT) and exhorted them and reminded them. He praised and glorified All
Grade:

Hadith #1627 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“When the Messenger of Allah (ﷺ) got up to pray tahajjud at night, he would brush his teeth with the siwak.
Grade:

Hadith #1661 - Sunan al-Nasa'i - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Aisha bint Abi Bakr; Hafs bin Ghyath حفص بن غياث; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Umar bin Sa'd bin 'Ubaid عمر بن سعد بن عبيد أبو داود (Sunan al-Nasa'i)
“The Prophet (ﷺ) did not die until most of his prayers were offered sitting down.”
Grade:

Hadith #1820 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“Whoever prays four rak’ahs before Zuhr and four after it, Allah (SWT) will forbid him from the Fire.”
Grade:

Hadith #2058 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“O Messenger of Allah, why will the believers be tested in their graves except the martyr?” He said: “The flashing of the swords above his head is trial enough.”
Grade:

Hadith #2075 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“When one of you dies he is shown his place morning and evening. If he is one of the people of paradise them he is one of the people of Paradise, and if he is one of the people of Hell, then he is one of the people of Hell, until Allah, the Mighty and Sublime, raises him up on the Day of Resurrection.”
Grade:

Hadith #2508 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
the Messenger of Allah enjoined Zakatul-Fitr at the end of Ramadan upon the people; a Sa’ of dates or a Sa’ of barley, upon everyone, free or slave, male or female, of the Muslims.
Grade:

Hadith #2515 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
I heard Ibn ‘Abbas deliver a Khutbah from your Minbar – meaning the Minbar in Al-Basrah – saying: ‘Sadaqatul Fitr is a Sa’ of food.” (Sahih) Abu ‘Abdur-Rahman (An-Nasa’i) said: This is the most reliable of the three.
Grade:

Hadith #2729 - Sunan al-Nasa'i - Abdul 'Aziz bin Suhaib عبد العزيز بن صهيب البناني; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Mjahd bin Musa مجاهد بن موسى; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم; Yahya bin Abi Ishaq يحيى بن أبي إسحاق; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
A similar report was narrated from Shu’bah with the same chain.
Grade:

Hadith #2731 - Sunan al-Nasa'i - Anas ibn Malik; Bakr bin 'Abdullah al-Mazni بكر بن عبد الله المزني; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan al-Nasa'i)
“The Messenger of Allah combined Hajj and “Umrah, then he passed away before he could forbid that, and before Qur’an was revealed forbidding it.
Grade:

Hadith #2801 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan al-Nasa'i)
“I used to twist the garlands fro the Hadi of the Messenger of Allah and the Hadi would be taken out garlanded, and the Messenger of Allah would stay (with his family) his wives.”
Grade:

Hadith #2839 - Sunan al-Nasa'i - Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; ibn Abbas; Mujahid bin Jabir مجاهد بن جبر (Sunan al-Nasa'i)
“A man said: “O Messenger of Allah, what animals may we kill when we are in Ihram?’ He said: “there are five for which there is no sin in killing them: Kites, crows, mice, scorpions and vicious dogs.'”
Grade:

Hadith #2840 - Sunan al-Nasa'i - Ahmed bin Ishaq bin al-Husain أحمد بن إسحاق بن الحصين; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; ibn Abbas; Ikrama عكرمة; Muhammad bin Ishaq al-Saghani محمد بن إسحاق الصغاني (Sunan al-Nasa'i)
the Prophet was asked what the Muhrim may kill. He said: “He may kill scorpions the evil creature (mice), Kites, crows and vicious dogs.”
Grade:

Hadith #3096 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
Abu Hurairah told him that the Messenger of Allah said: “I have been commanded to fight the people until they say La ilaha illallah (there is none worthy of worship except Allah). Whoever says La ilaha illallah, his life and his property are safe from me, except by its right (in cases where Islamic laws apply), and his reckoning will be with Allah.”
Grade:

Hadith #3192 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘Whoever spends in the cause of Allah, it will be recorded for him seven hundred fold.'”
Grade:

Hadith #3335 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Imran bin Husain (Sunan al-Nasa'i)
“I said: ‘O Messenger of Allah, how can I pay back the dues of the one who breast-fed me?’ He said: ‘By giving a male or female slave.'”
Grade:

Hadith #3336 - Sunan al-Nasa'i - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي (Sunan al-Nasa'i)
I married a woman, then a black woman came to us and said: I breast-fed you both. I went to the Prophet and said: I married so and so and a black woman came to me and said: I breast-fed you both. He turned away from me so I came to him from the other side and said: She is lying. He said: “How can you be intimate with your wife when she says that she breast-fed you both? Leave her (divorce her).”
Grade:

Hadith #3351 - Sunan al-Nasa'i - al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever manumits his female slave, then marries her, he will have two rewards.'”
Grade:

Hadith #3374 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Sa'id bin Kathir bin 'Afayr سعيد بن كثير بن عفير; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan al-Nasa'i)
“The Messenger of Allah gave permission for Mut’ah, so I and another man went to a woman from Bani ‘Amir and offered ourselves to her (for Mut’ah). She said: ‘What will you give me?’ I said: ‘My Rida’ (upper garment).’ My companion also said: ‘My Rida’.’ My companion’s Rida’ was finer than mine, but I was younger than him. When she looked at my companion’s Rida’ she liked it, but when she looked at me, she liked me. Then she said: ‘You and your Rida’ are suffi
Grade:

Hadith #3381 - Sunan al-Nasa'i - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Anas ibn Malik; Ayoub bin Sulaiman bin Bilal أيوب بن سليمان بن بلال; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“I got married to Fatimah, may Allah be pleased with her, and I said: ‘O Messenger of Allah, let me consummate the marriage.’ He said: ‘Give her something.’ I said: ‘I do not have anything.’ He said: ‘Where is your Hutami armor?’ I said: ‘It is with me.’ He said: ‘Give it to her.'”
Grade:

Hadith #3382 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“When Ali, may Allah be pleased with him, married Fatimah, may Allah be pleased with her, the Messenger of Allah said to him: ‘Give her something.’ He said: ‘I do not have anything.’ He said: ‘Where is your Hutami armor?'”
Grade:

Hadith #3388 - Sunan al-Nasa'i - Ahmed bin Yahya bin al-Wzyr أحمد بن يحيى بن الوزير; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Sa'id bin Kathir bin 'Afayr سعيد بن كثير بن عفير; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan al-Nasa'i)
“The Prophet stayed between Khaibar and Al-Madinah for three days when he consummated his marriage to Safiyyah bint Huyayy, and I invited the Muslims to his Walimah, in which there was no bread or meat. He commanded that a leather cloth (be spread) and dates, cottage cheese and ghee were placed on it, and that was his Walimah. The Muslims said: ‘(Will she be) one of the Mothers of the Believers, or a female slave whom his right hand possesses?’ They said: ‘If he has a Hijab for her, then
Grade:

Hadith #3456 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
“Buy her and set her free, for Al-Wala’ is to the one who sets the slave free.” Some meat was brought and it was said: “This is some of that which was given in charity to Barirah.” He said: “It is charity for her and a gift for us.” And the Messenger of Allah gave her the choice, and her husband was a free man.
Grade:

Hadith #3538 - Sunan al-Nasa'i - al-Laith bin Sa'd الليث بن سعد; al-Rabi' bin Sulaiman الربيع بن سليمان; Ayoub bin Musa bin 'Amr bin Sa'id أيوب بن موسى بن عمرو; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Shu'aib bin al-Laith bin Sa'd شعيب بن الليث بن سعد; Zaynab bint Abi Salamah (Sunan al-Nasa'i)
“My husband died in Al-Qadum, so I went to the Prophet and told him that our house was remote.” He gave her permission then he called her back and said: “Stay in your house for four months and ten days, until the term prescribed is fulfilled.”
Grade:

Hadith #3588 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
“A mule was given as a gift to the Messenger of Allah and he rode it.” ‘Ali said: “If we mate a donkey with a horse, we will have one like this.” The Messenger of Allah said: “That is only done by those who do not know.”
Grade:

Hadith #3590 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Imran bin Husain; Muhammad bin 'Abdullah محمد بن عبد الله بن بزيع; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“Whoever keeps a horse for the cause of Allah out of faith in Allah and believing the promise of Allah, its feed, water, urine and dung will all count as Hasanat in the balance of his deeds.”
Grade:

Hadith #3592 - Sunan al-Nasa'i - Amr bin 'Uthman bin Sa'id bin Kahtir عمرو بن عثمان بن سعيد بن كثير; Anas ibn Malik; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
It was narrated from Ibn ‘Umar that the Messenger of Allah organized a race for horses that had been made lean, from Al-Hafya’ and its finish line was Thaniyyat Al-Wada’, and he organized another race for horses that had not been made lean, from Ath-Thaniyyah to the Masjid of Banu Zuraiq, and ‘Abdullah was among those who took part in the race.
Grade:

Hadith #3672 - Sunan al-Nasa'i - al-Nu'man bin Bashir ibn Sa'd; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Muhammad bin Mansur bin Da'ud محمد بن منصور بن داود الطوسي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
“I said: ‘O Messenger of Allah, my mother has died; shall I give in charity on her behalf?’ He said: ‘Yes.’ I said: ‘What kind of charity is best?’ He said: ‘Providing drinking water.'”
Grade:

Hadith #3852 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hmad bin Ms'd'h al-Tmymy حماد بن مسعدة التميمي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan al-Nasa'i)
The Messenger of Allah said: “There is no vow at a moment of anger and its expiation is the expiation for an oath.”
Grade:

Hadith #3853 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan al-Nasa'i)
The Messenger of Allah said: “There is no vow at a moment of anger and its expiation is the expiation for an oath.” It was said: “Az-Zubair did not hear this Hadith from ‘Imran bin Husain.”
Grade:

Hadith #3854 - Sunan al-Nasa'i - Ahmed bin Hafs bin 'Abdullah أحمد بن حفص بن عبد الله; Anas ibn Malik; Hafs bin 'Abdullah bin Rashid حفص بن عبد الله بن راشد; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ibrahim bin Tahman إبراهيم بن طهمان; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan al-Nasa'i)
“I accompanied ‘Imran bin Husain, who said: ‘I heard the Messenger of Allah say: Vows are of two types: A vow that is made to do an act of obedience to Allah; that is for Allah and must be fulfilled, and a vow that is made to do an act of disobedience to Allah; that is for Shaitan and should not be fulfilled, and its expiation is the expiation for an oath.'”
Grade:

Hadith #3955 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
“The wives of the Prophet sent Zainab and she asked him permission to enter and she entered.” And she said something similar. Ma’mar contradicted the two of them; he reported it from Az-Zuhri, from ‘Urwah, from ‘Aishah.
Grade:

Hadith #3966 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Harun bin Muhammad bin Bkar هارون بن محمد بن بكار بن بلال; Muhammad bin 'Isa bin al-Qasim محمد بن عيسى بن القاسم (Sunan al-Nasa'i)
“Eat; your mother got jealous,” twice. Then the Messenger of Allah took the dish of ‘Aishah and sent it to Umm Salamah and he gave the dish of Umm Salamah to ‘Aishah.
Grade:

Hadith #3967 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hiban bin Hilal حبان بن هلال; Muhammad bin Hatim Al-Samayn محمد بن حاتم البغدادي - السمين (Sunan al-Nasa'i)
“I never saw any woman who made food like Safiyyah. She sent a dish to the Prophet in which was some food, and I could not keep myself from breaking it. I asked the Prophet what the expiation was for that, and he said: ‘A dish like that dish, and food like that food.'”
Grade:

Hadith #3968 - Sunan al-Nasa'i - Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Maymun bin Syah ميمون بن سياه; Muhammad bin 'Abdullah al-Ansari محمد بن عبد الله بن المثني - الأنصاري; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
“I perceive the smell of Maghafir (a nasty-smelling gum) on you; have you eaten Maghafir?” He came in to one of them, and she said that to him. He said: “No, rather I drank honey at the house of Zainab bint Jahsh, but I will never do it again.” Then the following was revealed: ‘O Prophet! Why do you forbid (for yourself) that which Allah has allowed to you.’ ‘If you two turn in repentance to Allah, (it will be better for you)’ about ‘Aishah and Hafsah, ‘And (remember) when th
Grade:

Hadith #4028 - Sunan al-Nasa'i - Abdullah bin 'Umar bin Hafs bin 'Asim عبد الله بن عمر بن حفص بن عاصم; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“Aishah said: ‘O ‘Ammar! Do you not know that it is not permissible to shed the blood of a Muslim except in three cases: a life for a life, a man who commits adultery after being married.'”
Grade:

Hadith #4029 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“We were with ‘Uthman when he was under siege and we could hear what was said from Al-Balat. ‘Uthman came in one day, then he came out, and said: ‘They are threatening to kill me.’ We said: ‘Allah will suffice you against them.’ He said: ‘Why would they kill me? I heard the Messenger of Allah say: It is not permissible to shed the blood of a Muslim except in one of three cases: A man who reverts to Kufr after becoming Muslim, or commits adultery after being married, or one who k
Grade:

Hadith #4030 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
“I saw the Prophet , then kill him, for the Hand of Allah is with the Jama’ah, and the Shaitan is with the one who splits away from the Ummah, running with him.'”
Grade:

Hadith #4031 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
“The Prophet when they are all united, kill him, no matter who he is among the people.'”
Grade:

Hadith #4386 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan al-Nasa'i)
” The Messenger of Allah commanded us to examine the eyes and ears (of animals for sacrifice).”
Grade:

Hadith #4526 - Sunan al-Nasa'i - al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan al-Nasa'i)
“The Messenger of Allah forbade two kinds of garments, and he forbade two kinds of transactions for us: Munabadhah and Mulamasah, which are kinds of transactions which were common during the Jahiliyyah.”
Grade:

Hadith #4752 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد (Sunan al-Nasa'i)
“A girl went out wearing some jewelry and a Jew caught her, crushed her head between two rocks and took the jewelry that she was wearing. She was found as she was breathing her last, and she was brought to the Messenger of Allah who said: ‘Who killed you? Was it so and so?’ She gestured no with her head, and he continued asking until he named the Jew, and she gestured yes with her head. He was caught and he confessed (to his crime), then the Messenger of Allah ordered that his head be crus
Grade:

Hadith #4756 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري (Sunan al-Nasa'i)
“What the people have been hearing from you has become widespread. If the Messenger of Allah told you anything, then tell us,” He said: “The Messenger of Allah did not tell me anything that he did not tell the people, except that in the sheath of my sword there is a sheet, in which it says: ‘The lives of the believers are equal in value, and they hasten to support the asylum granted by the least of them. But no believer may be killed in return for a disbeliever, nor one with a covenant w
Grade:

Hadith #4757 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever kills a Mu’ahad with no justification, Allah will forbid Paradise to him.”
Grade:

Hadith #4800 - Sunan al-Nasa'i - al-Qasim bin Rabi'ya bin Jwshn القاسم بن ربيعة بن جوشن; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Sahl bin Yusuf al-Anmaty سهل بن يوسف الأنماطي (Sunan al-Nasa'i)
“Whoever is killed in the blind or by something thrown, with a rock, a whip, or a stick, then the blood money to be paid for him is the blood money for accidental killing. Whoever kills deliberately, then retaliation is upon him, and whoever tries to prevent that, upon him is the curse of Allah, the Angels and all the people, and Allah will not accept any Sarf nor ‘Adl from him.”
Grade:

Hadith #4989 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“If a slave steals, then sell him, even for half price.” (Hasan) Abu ‘Abdur-Rahman (An-Nasai) said: ‘Umar bin Abi Salamah is not strong in Hadith.
Grade:

Hadith #5003 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hiban bin Hilal حبان بن هلال; Muhammad bin Hatim Al-Samayn محمد بن حاتم البغدادي - السمين (Sunan al-Nasa'i)
The Prophet commanded him to call out on the days of At-Tashriq that no one would enter Paradise except a believer, and that these were the days of eating and drinking.
Grade:

Hadith #5198 - Sunan al-Nasa'i - al-Hasan bin Salah bin Salah الحسن بن صالح بن صالح; Anas ibn Malik; Asim al-Ahwal عاصم الأحول; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Khalid bin محمد بن خالد; Salmah bin 'Abdul Malik سلمة بن عبد الملك العوصي (Sunan al-Nasa'i)
A man was sitting with the Prophet saw him after that and said: “What happened to the ring?” He said: “I threw it away.” He said: “I did not tell you to do that, rather I told you to sell it and benefit from its price.” This Hadith is Munkar.
Grade:

Hadith #5199 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Umayya bin Bustam أمية بن بسطام (Sunan al-Nasa'i)
The Prophet looked away, he threw it away. He said: “I think that he hurt you or we made you lose money.”
Grade:

Hadith #5200 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Musa bin Da'ud al-Dby موسى بن داود الضبي أبو عبد الله; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
A man, among those who met the Prophet , wore a gold ring. A similar report.
Grade:

Hadith #5234 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan al-Nasa'i)
“The Messenger of Allah said to me: ‘Five things are from the Fitrah: Trimming the mustache, plucking the armpit hairs, clipping the nails, shaving the pubes and circumcision.'”
Grade:

Hadith #5280 - Sunan al-Nasa'i - al-Hasan bin Salah bin Salah الحسن بن صالح بن صالح; al-Qasim bin Zakaria bin Yahya القاسم بن زكريا بن يحيى البغدادي; Anas ibn Malik; Asim al-Ahwal عاصم الأحول; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“The Messenger of Allah forbade me from four things: Wearing garments dyed with safflower, and from wearing gold rings, and from wearing Al-Qassiyah garments, and reciting Qur’an while I am bowing.”
Grade:

Hadith #5388 - Sunan al-Nasa'i - Abu Bakra al-Thaqafi; al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
The Prophet said: “Those who are just and fair will be with Allah, Most High, on thrones of light, at the right hand of the Most Merciful, those who are just in their rulings and in their dealings with their families and those of whom they are in charge.” Muhammad (one of the narrators) said in his Hadith: “And both of His hands are right hands.”
Grade:

Hadith #5451 - Sunan al-Nasa'i - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك (Sunan al-Nasa'i)
The Prophet used to seek refuge (with Allah) from four things: From knowledge that is of no benefit, from a heart that does not feel humble, from a supplication that is not heard, and a soul that is never satisfied.
Grade:

Hadith #5457 - Sunan al-Nasa'i - Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
The Messenger of Allah used to say: “Allahumma inni a’udhu bika minal-‘ajzi, wal-kasali, wal-bukhli, wal-harami, ‘adhabil-qabr wa fitnatil-mahya wal-mamat (O Allah, I seek refuge in You from incapacity and laziness, and miserliness and old age, and the torment of the grave, and the trials of life and death.)”
Grade:

Hadith #5495 - Sunan al-Nasa'i - al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan al-Nasa'i)
When the Prophet went out of his house, he said: “Bismillahi Rabbi! A’udhu bika min an azilla aw adilla aw azlima aw uzlama, aw ajhala aw yujhala ‘alayya (In the name of Allah, my Lord, I seek refuge in You from falling into error or going astray, or wrongdoing (others) or being wronged, and from behaving or being treated in an ignorant manner.)”
Grade:

Hadith #5543 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“I looked for the Messenger of Allah one night in my bed, and I did not find him. I struck my hand on the head of the bed, and my hand fell on the soles of his feet. He was prostrating and saying: ‘A’udhu bi ‘afwika min ‘iqabika, wa a’udhu bi ridaka min sakhatika, wa a’udhu bika minka (I seek refuge in Your forgiveness from Your punishment, and I seek refuge in Your pleasure from Your wrath, and I seek refuge in You from You.)'”
Grade:

Hadith #5558 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; ibn Abbas; Ikrama عكرمة; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ad-Dubba’, Al-Muzaffat,” – and on one occasion he added: “An-Naqir,” – “and (he forbade) mixing At-Tamr (dried dates) with raisins, and Az-Zahuw with At-Tamr.”
Grade:

Hadith #5565 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
The Messenger of Allah forbade soaking raisins and dried dates together, and he forbade soaking Al-Busr and dried dates together.
Grade:

Hadith #2122 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Uthman bin Muhammad; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) married Umm Salamah, he stayed with her three night, and said: Your people (i.e. clan) are not being humbled for you in my estimation. If you wish I shall stay with you seven nights; and if I stay with you seven nights, I shall stay with my other wives seven nights.
Grade: Sahih

Hadith #2404 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan Abi Dawud)
The Prophet (ﷺ) left Medina for Mecca till he reached ‘Usfan, He then called for a vessel (of water). It was raised to his mouth to show it to the people, and that was in Ramadan. Ibn ‘Abbas used to say: The Prophet (ﷺ) fasted and he broke his fast. He who likes may fast and he who likes may break.
Grade: Sahih

Hadith #2503 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who does not join the warlike expedition (jihad), or equip, or looks well after a warrior’s family when he is away, will be smitten by Allah with a sudden calamity. Yazid ibn Abdu Rabbihi said in his tradition: ‘before the Day of Resurrection”.
Grade: Hasan

Hadith #2507 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Anas bin Malik موسى بن أنس بن مالك; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
Zaid bin Thabit said “I was beside the Apostle of Allaah(ﷺ) when the divinely-inspired calmness overtook him and the thigh of the Apostle of Allaah(ﷺ) fell on my thigh. I did not find any weightier than the thigh of the Apostle of Allaah(ﷺ). He then regained his composure and said “Write down. I wrote on a shoulder. Not equal are thise believers who sit (at home), other than those who have a (disabling) hurt, and those who strive in the way of Allaah. When Ibn Umm Makhtum who was blind
Grade: Hasan Sahih

Hadith #2580 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Imran bin Husain; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Unbasa bin Sa'id bin al-Aas عنبسة بن سعيد بن العاص بن سعيد; Yahya bin Khlf al-Bahly يحيى بن خلف الباهلي أبو سلمة البصري (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Al Zuhri with the chain of ‘Abbad and to the same affect. Abu Dawud said “This tradition has also been narrated by Ma’mar, Shu’aib and ‘Aqil on the authority of Al Zuhri from a number of scholars and this is the soundest one in our opinion.
Grade: Da'if

Hadith #2640 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Sa'id bin Y'aqub al-Talqany سعيد بن يعقوب الطالقاني (Sunan Abi Dawud)
Abu Hurairah reported the Apostle of Allaah(ﷺ) as saying “ I am commanded to fight with men till they testify that there is no god but Allaah, when they do that they will keep their life and property safe from me, except what is due to them. (i.e., life and property) and their reckoning will be at Allaah’s hands.”
Grade: Sahih

Hadith #2641 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
The Prophet (ﷺ) said: I am commanded to fight with men till they testify that there is no god but Allah, and that Muhammad is His servant and His Apostle, face our qiblah (direction of prayer), eat what we slaughter, and pray like us. When they do that, their life and property are unlawful for us except what is due to them. They will have the same rights as the Muslims have, and have the same responsibilities as the Muslims have.
Grade: Sahih

Hadith #3025 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; Ahmed bin 'Ali al-Nmyry أحمد بن علي النميري; al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة (Sunan Abi Dawud)
Wahb said: I asked Jabir about the condition of Thaqif when they took the oath of allegiance. He said: They stipulated to the Prophet (ﷺ) that there would be no sadaqah (i.e. zakat) on them nor Jihad (striving in the way of Allah). He then heard the Prophet (ﷺ) say: Later on they will give sadaqah (zakat) and will strive in the way of Allah when they embrace Islam.
Grade: Sahih

Hadith #3300 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
While the Prophet (ﷺ) was preaching a man was standing in the sun. He asked about him. They said: He is Abu Isra’il who has taken a vow to stand and not to sit, or go into shade, or speak, but to fast. Thereupon he said: Command him to speak, to go into the shade, sit and complete his fast.
Grade: Sahih

Hadith #3370 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade the sale of fruits until they are ripened (tushqihah). He was asked: What do you mean by their ripening (ishqah)? He replied: They become red or yellow, and they are eaten.
Grade: Sahih

Hadith #3423 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) got him self cupped and gave the cupper his wages. Had he considered it impure, he would not have given it (wage) to him.
Grade: Sahih

Hadith #3450 - Sunan Abi Dawud - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Uthman bin Muhammad (Sunan Abi Dawud)
A man came and said: Messenger of Allah, fix prices. He said: (No), but I shall pray. Again the man came and said: Messenger of Allah, fix prices. He said: It is but Allah Who makes the prices low and high. I hope that when I meet Allah, none of you has any claim on me for doing wrong regarding blood or property.
Grade: Sahih

Hadith #3533 - Sunan Abi Dawud - Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Yazid bin Zari' يزيد بن زريع; Yusuf bin Mahk يوسف بن ماهك الفارسي (Sunan Abi Dawud)
Hind came to the Prophet (ﷺ) and said: Messenger of Allah, Abu Sufyan is a stingy person. Is there any harm to me if I spend on his dependants from his property without his permission ? The Prophet (ﷺ) replied: There is no harm to you if you spend according to the custom.
Grade: Sahih

Hadith #3566 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to me: When my messengers come to you, give them thirty coats of mail, and thirty camels. I asked: Messenger of Allah, is it a loan with a guarantee of its return, or a loan to be paid back? He replied : It is a loan to be paid back.
Grade: Sahih

Hadith #4185 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
The hair of the Messenger of Allah (ﷺ) were up to the lobes of his ears.
Grade: Sahih

Hadith #4216 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
The signet-ring of the Prophet (ﷺ) was of silver with an Abyssinian stone.
Grade: Sahih

Hadith #4245 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Nsr bin 'Asim al-Lythy نصر بن عاصم الليثي البصري; Sulaiman bin al-Mughira al-Qaysy سليمان بن المغيرة القيسي مولاهم (Sunan Abi Dawud)
I (Hudhaifah) asked : Will any be spared after the use of the sword ? He replied: There will be remnant with specks in its eye and an illusory truce. He then transmitted the rest of the tradition. Qatadah applied this to the apostasy during the Caliphate of Abu Bakr. The word aqdha’ (sing. qadhan) means specks, hudnah means truce and dakhan means malice.
Grade: Hasan

Hadith #4365 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
So he (the prophet) order nails to be heated and had them blinded with them, and he had their hands and feet cut off, and did not cauterise them to stop the flow of blood.
Grade: Sahih

Hadith #4615 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hilal bin Bashr bin Mhbwb هلال بن بشر بن محبوب (Sunan Abi Dawud)
“And for this did He create them.” He said: He created these for this and those for that.
Grade: Sahih

Hadith #4616 - Sunan Abi Dawud - Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
“Can lead (any) into temptation concerning Allah, except such as are (themselves) going to the blazing fire.” He said: Except the one whom Allah destined that he should go to Hell.
Grade: Sahih

Hadith #4617 - Sunan Abi Dawud - Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Al-Hasan used to say that his fall from the heaven on the earth is dearer to him than uttering: The matter is in my hand.
Grade: Da'if

Hadith #4801 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
neither the Jawwaz nor the Jazari will enter paradise. He said that the Jawwaz is the one who is coarse and uncivil.
Grade: Sahih

Hadith #4805 - Sunan Abi Dawud - Abdullah bin Mughfal al-Mazni; al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
You have beheaded your friend (saying it three times). He then said : One who cannot help expressing praise of his companion, should say : I consider him such and such (as he intends to say), but I do not declare him pure with Allah.
Grade: Sahih

Hadith #4816 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Kathir bin 'Ubaid bin Nmyr كثير بن عبيد بن نمير المذحجي; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري; Muhammad bin 'Isa bin al-Tibaa' محمد بن عيسى بن الطباع (Sunan Abi Dawud)
And guiding the people on their way.
Grade: Hasan Sahih

Hadith #4861 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) called me. He intended to send me with some goods to AbuSufyan to distribute among the Quraysh at Mecca after the conquest. He said: Search for a companion. Then Amr ibn Umayyah ad-Damri came to me and said: I have been told that you are intending to make a journey and are seeking a companion. I said: Yes. He said: I am your companion. I then went to the Messenger of Allah (ﷺ) and said: I have found a companion. He asked: Who is he? I replied: Amr ibn Umayyah ad-Da
Grade: Da'if

Hadith #4996 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
I bought something from the Prophet (ﷺ) before he received his Prophetic commission, and as there was something still due to him I promised him that I would bring it to him at his place, but I forgot. When I remembered three days later, I went to that place and found him there. He said: You have vexed me, young man. I have been here for three days waiting for you. Abu Dawud said: Muhammad b. Yahya said : This is, in our opinion, ‘Abd al-Karim b. ‘Abd Allah b. Shaqiq (instead of “from ‘
Grade: Da'if

Hadith #5201 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Abi Dawud)
Umar came to the Prophet (ﷺ) when he was in his wooden oriel, and said to him: Peace be upon you. Messenger of Allah, peace be upon you! May Umar enter ?
Grade: Sahih

Hadith #5211 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: If two Muslims meet, shake hands, praise Allah, and ask Him for forgiveness, they will be forgiven.
Grade: Da'if

Hadith #58 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Hmyd bin Hyan محمد بن حميد بن حيان; Salmah bin al-Fadl al-Abrash سلمة بن الفضل الأبرش (Jami' al-Tirmidhi)
“The Prophet would perform wudu for every Salat, whether he was in state of purity or not in a state of purity.”
Grade:

Hadith #72 - Jami' al-Tirmidhi - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; al-Hasan bin Muhammad al-Za'farani الحسن بن محمد الصباح الزعفراني; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Jami' al-Tirmidhi)
“Some people from Urainah arrived in Al-Madinah, and they were uncomfortable (and ill from the climate). So Allah’s Messenger sent them some camels from charity. He told them: “Drink from their milk and urine.” So they killed the camel driver that Allah’s Messenger sent, and they violently drove off the camels, and apostatized from Islam. So the Prophet came to them, he cut off their hands and feet on opposite side, and branded their eyes, and threw them in Al-Harrah.” Anas said, “
Grade:

Hadith #121 - Jami' al-Tirmidhi - Abu Hurairah; Abu Rafi'; Bakr bin 'Abdullah al-Mazni بكر بن عبد الله المزني; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Jami' al-Tirmidhi)
the Prophet met him while he was Junub. He said: ” I withdrew – to perform Ghusl. Then he returned, so he said: ‘Where have you been?’ Or: ‘Where did you go?’ I replied: ‘I was Junub.’ So he said: ‘Indeed the believer is not defiled.”’
Grade:

Hadith #363 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Talha bin Masraf محمد بن طلحة بن مصرف; Shababa bin Sawar شبابة بن سوار الفزاري; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Jami' al-Tirmidhi)
“Allah’s Messenger performed Salat during his illness behind Abu Bakr while seated, wrapped in a garment.”
Grade:

Hadith #376 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Jami' al-Tirmidhi)
Allah’s Messenger said: “Indeed I hear the crying of a small boy while I am in Salat, so I shorten it in fear that his mother may be tormented.”
Grade:

Hadith #690 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري (Jami' al-Tirmidhi)
“The Messenger of Allah vowed to stay away from his wives for a month, so he stayed in a loft for twenty-nine days. They said: ‘O Messenger of Allah, your vow was for a month,’ so he said: ‘The month is twenty-nine (days).'”
Grade:

Hadith #769 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري (Jami' al-Tirmidhi)
Anas bin Malik was asked about the Prophet’s fasting and he said: “He would fast during a month until we thought that he did not want to abstain from fasting during any of it. And, he would not fast during a month until we thought that he did not want to fast during any of it. (There was no time) that I wanted to see if he was performing Salat during the night, except that I would see him praying, nor to see him sleeping, except that I would see him sleeping.”
Grade:

Hadith #803 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin Bashar Bindar محمد بن بشار بندار (Jami' al-Tirmidhi)
“The Prophet would perform I’tikaf during the last ten (nights) of Ramadan. One year he did not perform I’tikaf, so he performed I’tikaf for twenty (nights) in the following year.”
Grade:

Hadith #821 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Jami' al-Tirmidhi)
“the Messenger of Allah performed the Ifrad form of Hajj.”
Grade:

Hadith #1056 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Yazid bin Harun يزيد بن هارون (Jami' al-Tirmidhi)
“Indeed the Messenger of Allah cursed the women who visit the graves.”
Grade:

Hadith #1274 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري (Jami' al-Tirmidhi)
That the Prophet (ﷺ) said: “Do not go out to meet the market (caravan), do not leave animals un-milked (to deceive the buyer), nor out-spend one another.” There are narrations on this topic from Ibn Mas’ud and Abu Hurairah. The Hadith if Ibn ‘Abbas is a Hasan Sahih Hadith. This is acted upon according to the people of knowledge, they dislike selling the Muhaffalah, and it is the Musarrah that has not been milked by its owner in days or more than that, so the milk accumulates in its ud
Grade:

Hadith #1310 - Jami' al-Tirmidhi - Anas ibn Malik; Hajjaj bin al-Minhal حجاج بن المنهال; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Jami' al-Tirmidhi)
Rafi’ bin Khadij and Sahl bin Abi Hathmah narrated to him that the Messenger of Allah (ﷺ) prohibited Al-Muzabanah sales, (buying) fruits with dried dates, except for those who practice Al-‘Araya – for he permitted it for them – and from buying grapes with raisins, and from every fruit by its estimation. This Hadith is Hasan Sahih Gharib from this route.
Grade:

Hadith #1347 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umar bin Sa'd bin 'Ubaid عمر بن سعد بن عبيد أبو داود (Jami' al-Tirmidhi)
“Whoever frees a portion” or, he said: “a part” or he said: “a share he owns of a slave, then he can afford the remainder of the price according to the reasonable price, then he will be free. Otherwise he has freed as much as he has freed (only).” Ayyub (one of the narrators) said: “Perhaps Nafi said in this Hadith: ‘Meaning he has freed as much of him as he has freed.'”
Grade:

Hadith #1348 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Suwayd bin 'Abdul 'Aziz سويد بن عبد العزيز بن نمير (Jami' al-Tirmidhi)
“Whoever frees a portion of a slave he owns, then he can afford the remainder of the price, then he should free him with his wealth.”
Grade:

Hadith #1507 - Jami' al-Tirmidhi - Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Imran bin Da'ud al-'Ami Abu al-'Awwam عمران بن داود العمي أبو العوام القطان (Jami' al-Tirmidhi)
“The Messenger of Allah (ﷺ) prohibited that an animal with a A’dab (stump) horn or ear should be slaughtered as a sacrifice.” Qatadah (one of the narrators) said: “So I mentioned this to Sa’eed bin Al-Musayyab and he said: ‘The A’dab is that which equals or more than that.'”
Grade:

Hadith #1508 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Jami' al-Tirmidhi)
“I asked Abu Abyub how the slaughtering was done during the time of the Messenger of Allah (ﷺ). He said: ‘A man would sacrifice a sheep for himself and the people in his household. They would eat from it and feed others, until the people (later) would boast about it and it became as you see now.”
Grade:

Hadith #1521 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Ma'n bin 'Isa bin Yahya معن بن عيسى بن يحيى; Muhammad bin 'Abdullah al-Ansari محمد بن عبد الله بن المثني - الأنصاري (Jami' al-Tirmidhi)
That the Messenger of Allah (ﷺ) said: “The best of Udhiyah (sacrifice) is a ram, and the best (burial) shroud is the Hullah.”
Grade:

Hadith #1580 - Jami' al-Tirmidhi - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Muhammad bin Rafa'i محمد بن رافع (Jami' al-Tirmidhi)
That the Messenger of Allah (ﷺ) said: “Whoever dies and he is free of three: Kibr (Pride), Ghulul, and debt, he will enter paradise.” There are narrations on this topic from Abu Hurairah and Zaid bin Khalid Al-Juhni Footnote: Ghulul refers to goods stolen from the spoils of war, or concealed, before it is divided among the soldiers
Grade:

Hadith #1604 - Jami' al-Tirmidhi - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Jami' al-Tirmidhi)
That the Messenger of Allah (ﷺ) said: “Three will not be spoken to by Allah on the Day of Judgement, nor will they be purified, and for them is a painful torment: A man that gave a pledge to an Imam, and if he gives to him he fulfills it, and if he does not give to him he does not fulfill not fulfill it.” This Hadith is Hasan Sahih.
Grade:

Hadith #1607 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري (Jami' al-Tirmidhi)
“We used to say that the participants of Badr on the Day of Badr were like the number of companions of Talut, three hundred and thirteen men.” There is something on this topic from Ibn ‘Abbas. This Hadith is Hasan Sahih. Ath-Thawri and others reported it from Abu Ishaq.
Grade:

Hadith #1615 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري (Jami' al-Tirmidhi)
Similar to the narration of Abu Mu’aqiyah (no. 1604) but he did not mention in it: “from Jarir” in it, and that is more correct. There is something on this topic from Samurah. Most of the companions of Isma’il said: “From Isma’il, from Qais bin Abu Hazim, that the Messenger of Allah (ﷺ) sent a military expedition.” and they did not mention: “from Jarir” in it. Hammad bin Salamah reported similar to the narration of Abu Mu’awiyah, from Al-Hajjaj bin Artah, from Isma’il bi
Grade:

Hadith #1691 - Jami' al-Tirmidhi - Anas ibn Malik; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Jami' al-Tirmidhi)
“The hand-guard on the sword of the Messenger of Allah (ﷺ) was made from silver.” This Hadith is Hasan Gharib. This is how it has been reported from Hamam from Qatadah from Anas. While some of them reported it from Qatadah, from Sa’eed bin Abu Al-Hasan who said: “The hand-guard on the sword of Messenger of Allah (ﷺ) was made from silver.”
Grade:

Hadith #1705 - Jami' al-Tirmidhi - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك (Jami' al-Tirmidhi)
That the Prophet (ﷺ) said: “Indeed each of you is a shepherd and all of you will be questioned regarding your flock. The commander who is in authority over the Muslims is responsible and he will be questioned regarding his responsibility. The man is responsible over the inhabitants of his house and he is the one who will be questioned about them. The wife is responsible in her husband’s house and she will be questioned about it. The slave is responsible regarding his master’s property, a
Grade:

Hadith #1793 - Jami' al-Tirmidhi - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; al-Hasan bin Muhammad al-Za'farani الحسن بن محمد الصباح الزعفراني; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Jami' al-Tirmidhi)
From his father who said: “A man wearing an iron ring came to the Prophet (ﷺ). So he said to him: ‘What is this I see on you, jewelry of the people of the Fire ?’ Then he came wearing a ring of brass. So he said: ‘What is this smell of idols I sense on you ?’ Then he came wearing a ring of gold. So he said to him: ‘What is this jewelry of the people of Paradise I see on you ?’ So he said: ‘What should I use then ?’ He said: ‘From silver, but not its entire weight.” This
Grade:

Hadith #1992 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Jami' al-Tirmidhi)
“They said: ‘O Messenger of Allah! You joke with us?’ He said: ‘Indeed I do not say except what is true.'” (Hasan)’
Grade:

Hadith #2054 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Jami' al-Tirmidhi)
“There was no wound nor cut on the Messenger of Allah (S.A.W) but he would order me to put Hinna on it.” Another chain reports a similar narration.
Grade:

Hadith #2109 - Jami' al-Tirmidhi - Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; al-Hasan bin Muhammad al-Za'farani الحسن بن محمد الصباح الزعفراني; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Jami' al-Tirmidhi)
“‘Umar said: ‘The blood-money is upon the ‘Aqilah, and the wife does not inherit anything from the blood-money of her husband.’ So Ad-Dahhak bin Sufyan Al-Kilabi informed him that the Messenger of Allah(S.A.W) wrote to him, (saying) to give the wife of Ashyam Ad-Dababi the inheritance from her husband’s blood-money.'”
Grade:

Hadith #2223 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري (Jami' al-Tirmidhi)
“I was with Abu Bakrah under the Minbar of Ibn ‘Amir while he was giving a Khutbah wearing a fine garment. Abu Bilal said: ‘Look at our Amir wearing clothes of wickedness!’ So Abu Bakrah said: Be quiet! I heard the Messenger of Allah(s.a.w) saying: “Whoever insults Allah’s Sultan on the earth, Allah disgraces him.”
Grade:

Hadith #2315 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري (Jami' al-Tirmidhi)
“Glad tidings of Paradise.” To which the Messenger of Allah (s.a.w) said: “You do not know. Perhaps he spoke of what did not concern him or he was greedy with that which would not decrease him.”
Grade:

Hadith #2604 - Jami' al-Tirmidhi - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Abi 'Adi محمد بن أبي عدي (Jami' al-Tirmidhi)
“Should I not inform you about the people of Paradise: They are every humble and weak person, who if he were to make an Oath by Allah, He would fulfill it. Should I not inform you about the people of the Fire: They are every prideful, swaggering, ill-speaking person.”
Grade:

Hadith #2686 - Jami' al-Tirmidhi - Abdullah bin 'Abdur Rahman al-Daarimi عبد الله بن عبد الرحمن الدارمي; Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Jami' al-Tirmidhi)
that the Messenger of Allah (ﷺ) said: “The wise statement is the lost property of the believer, so wherever he finds it, then he is more worthy of it.”
Grade:

Hadith #2894 - Jami' al-Tirmidhi - Abdullah bin 'Abdur Rahman al-Daarimi عبد الله بن عبد الرحمن الدارمي; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة (Jami' al-Tirmidhi)
that the Messenger of Allah (ﷺ) said to a man among his Companions: “Have you married O so-and-so?” He said: “No by Allah O Messenger of Allah! And I do not have anything to marry with.” He said: “Do you not know: Qul Huwa Allahu Ahad?” He said: “Of course.” He said: “It is a third of the Qur’an.” He said: “Do you not know Idha Ja Nasrullahi Wal-Fath?” He said: “Of course.” He said: “It is a fourth of the Qur’an.” He said: “Do you not know Qul Ya Ayyuhal-K
Grade:

Hadith #3136 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Anas ibn Malik; Hajjaj bin al-Minhal حجاج بن المنهال; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Umar ibn al-Khattab (Jami' al-Tirmidhi)
that regarding the saying of Allah, Most High: “The Day when We shall call together all human beings with their (respective) Imam (17:71)” the Prophet (ﷺ) said: “One of you will be called out to be given his record in his right hand, he will be grown in his body to sixty forearm-lengths, his face will be whitened, and a crown of sparkling pearls will be placed upon his head. So he will go to his companions, who can see him from afar, and they will say: ‘O Allah! Bring this one to us, a
Grade:

Hadith #3137 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Umar ibn al-Khattab (Jami' al-Tirmidhi)
regarding Allah’s saying: “It may be that your Lord will raise you to a praised station (17:79)” that the Messenger of Allah (ﷺ) was asked about it and he said: “It is the intercession.”
Grade:

Hadith #3183 - Jami' al-Tirmidhi - Abdullah bin Bakr عبد الله بن بكر بن حبيب السهمي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج (Jami' al-Tirmidhi)
“I asked the Messenger of Allah (ﷺ) which sin is the worst.’ He said: ‘That you make an equal to Allah while it is He who created you, that you kill your child so that he not eat with you – or because of your food, that you commit adultery with your neighbor’s wife.'” He said: “And he recited this Ayah: ‘And those who invoke not any other god along with Allah, nor kill such life as Allah has forbidden, except for what is required, nor commit illegal sexual intercourse – and w
Grade:

Hadith #3188 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم (Jami' al-Tirmidhi)
“The Messenger of Allah (ﷺ) said to his uncle: ‘Say La Ilaha Illallah and I may bear witness with that, on your behalf, on the Day of Judgement.’ So he said: ‘If it weren’t that the Quraish would insult me (saying): “He only said it out of fright” then I would delight your eyes.’ Then Allah the Mighty and Sublime revealed: Verily, you guide not whom you like, but Allah guides whom He wills (28:56).”
Grade:

Hadith #3189 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Ahmed bin Manay' أحمد بن منيع; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Yazid bin Harun يزيد بن هارون (Jami' al-Tirmidhi)
that his father, Sa’d, said: “Four Ayat were revealed about me” and he mentioned the story. Umm Sa’d had said: “Did not Allah command you to honor (your parents). By Allah! I will not eat or drink anything until I die or you renounce (Islam).” He said: “So when they wanted to make her eat, they would force her mouth open. So this Ayah was revealed: And We have enjoined on man to be dutiful to his parents; but if they strive to make you associate (partners) with Me, of which you hav
Grade:

Hadith #3421 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Yazid bin Harun يزيد بن هارون (Jami' al-Tirmidhi)
“I have directed my face towards the One who has created the heavens and the earth, as a Hanif, and I am not of the idolaters. Indeed, my Salat, my sacrifice, my living, my dying, is for Allah, the Lord of all that exists, without partner, and with this have I been ordered and I am of the Muslims. O Allah, You are the King, there is none worthy of worship except You. You are My Lord, and I am Your slave, I have wronged myself and I admit to my sin, so forgive me all my sins, verily, there is n
Grade:

Hadith #3958 - Jami' al-Tirmidhi - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري (Jami' al-Tirmidhi)
that the Prophet (ﷺ) said: “People should stop boasting about their fathers who have died, while they are but coals of Hell, or they will be more humiliated with Allah than the dung beetle who rolls dung with his nose. Indeed Allah has removed the pride of Jahiliyyah from you, and its boasting about lineage. from dust.”
Grade:

Hadith #106 - Sunan Ibn Majah - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل (Sunan Ibn Majah)
the Prophet performed ablution with the water left over after she had taken a bath to cleanse herself from sexual impurity.
Grade:

Hadith #577 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Abu Rafi'; Bakr bin 'Abdullah al-Mazni بكر بن عبد الله المزني; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan Ibn Majah)
“We used to recite the Opening of the Book and a Surah behind the Imam in the first two Rak’ah of the Zuhr and the ‘Asr, and in the last wo Rak’ah (we would recite) the Opening of the Book.”
Grade:

Hadith #693 - Sunan Ibn Majah - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; Abdur Rahman bin Muhammad al-Maharbi عبد الرحمن بن محمد بن زياد المحاربي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade performing prayer behind one who is engaged in conversation or one who is sleeping.”
Grade:

Hadith #762 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Tryf bin Khlyf محمد بن طريف بن خليف (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) used to perform prayer on a Khumrah.”
Grade:

Hadith #784 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد (Sunan Ibn Majah)
“I saw the Messenger of Allah (ﷺ) performing prayer at Bi’r ‘Ulya, in a garment.”
Grade:

Hadith #915 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Bashar Bindar محمد بن بشار بندار (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘When you call upon Allah, then do so with the palms of your hands (upwards). Do not do so with the back of your hands (upwards). And when you finish, then wipe your face with them.’”
Grade:

Hadith #1030 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Ibn Majah)
“It is part of the Sunnah to walk to ‘Eid (prayers).”
Grade:

Hadith #1062 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Umar ibn al-Khattab (Sunan Ibn Majah)
“I met Abu Salamah bin ‘Abdur-Rahman and said: ‘Tell me a Hadith that you heard from your father, in which mention is made of the month of Ramadan.’ He said: ‘Yes, my father narrated to me that the Messenger of Allah (ﷺ) mentioned the month of Ramadan and said: “A month which Allah has enjoined upon you to fast, and in which I have established Qiyam (prayers at night) as Sunnah for you. So whoever fasts it and spends its nights in prayer out of faith and in hope of reward; he will
Grade:

Hadith #1156 - Sunan Ibn Majah - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل (Sunan Ibn Majah)
“I said: ‘O Messenger of Allah! Tell me of a deed that I can adhere to and act upon.’ He said: “You should prostrate, for you will not prostrate to Allah but He will raise you in status one degree thereby and erase from you one sin.”
Grade:

Hadith #1239 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Nasr bin 'Ali bin Nasr bin 'Ali; Sahl bin Yusuf al-Anmaty سهل بن يوسف الأنماطي (Sunan Ibn Majah)
“Zaid bin Arqan used to say the Takbir four times in the funeral prayer, and he said the Takbir five times for one funeral. I asked him (about that) and he said: ‘The Messenger of Allah (ﷺ) used to do that.’”
Grade:

Hadith #1286 - Sunan Ibn Majah - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر (Sunan Ibn Majah)
It was narrated from Abu Sa’eed that the Messenger of Allah (ﷺ) was brought into his grave from the direction of the Qiblah, and he was placed in his grave gently.
Grade:

Hadith #1294 - Sunan Ibn Majah - Bakr bin 'Abdullah al-Mazni بكر بن عبد الله المزني; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hamza bin al-Mughira bin Nashayt حمزة بن المغيرة بن نشيط; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Ibn Majah)
“Dig the grave deep, make it spacious and prepare it well.”
Grade:

Hadith #1504 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Ibn Jurayj ابن جريج (Sunan Ibn Majah)
The Prophet (ﷺ) used to spend the last ten days of Ramadan in I’tikaf. One year he was traveling, so the following year he spent twenty days in I’tikaf.
Grade:

Hadith #1624 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد (Sunan Ibn Majah)
the Prophet (ﷺ) married Aishah with the household goods the value of which was fifty Dirham.
Grade:

Hadith #2174 - Sunan Ibn Majah - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Umar bin Abd al-Wahd عمر بن عبد الواحد بن قيس السلمي (Sunan Ibn Majah)
“A mount may be ridden when it is pawned, and its milk may be drunk when it is pawned, but the one who rides it or milks it must pay for its upkeep.’ ”
Grade:

Hadith #2284 - Sunan Ibn Majah - Anas ibn Malik; Hajjaj bin al-Minhal حجاج بن المنهال; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Salama حماد بن سلمة; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Ibn Majah)
“When the woman stole the Qatifah from the house of the Messenger of Allah (ﷺ), we regarded that as a serious matter. She was a woman from Quraish. So we came to the Prophet (ﷺ) and spoke to him, and said: ‘We will ransom her for forty Uqiyyah.’ The Messenger of Allah (ﷺ) said: ‘Purification is better for her.” When we heard the Messenger of Allah (ﷺ) speak so kindly, we went to Usamah and said: ‘Speak to the Messenger of Allah (ﷺ) .’ When the Messenger of Allah (ﷺ) saw
Grade:

Hadith #2302 - Sunan Ibn Majah - Anas ibn Malik; Hajjaj bin al-Minhal حجاج بن المنهال; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Ibn Majah)
“If a slave woman commits fornication then whip her, and if she commits fornication then whip her, and if she commits fornication then whip her, then sell her even if that is for a rope.”
Grade:

Hadith #2596 - Sunan Ibn Majah - Abdullah bin al-Shakhayr; al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Matraf bin 'Abdullah bin al-Shakhayr مطرف بن عبد الله بن الشخير; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Ibn Majah)
“This is Abu Dharr,” so he (the slave) started to move back. But Abu Dharr said: “My close friend (i.e., the Prophet (ﷺ)) told me to listen and obey, even if (the leader was) an Ethiopian slave with amputated limbs.”
Grade:

Hadith #2674 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Ibn Majah)
It was narrated from Ibn ‘Umar that the Messenger of Allah (ﷺ) used to enter Makkah from the upper mountain pass and when he left, he would leave from the lower mountain pass.
Grade:

Hadith #2745 - Sunan Ibn Majah - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ishaq bin 'Abdullah bin Abi Farwa إسحاق بن عبد الله بن أبي فروة; Muhammad bin Rmh bin al-Mhajr محمد بن رمح بن المهاجر (Sunan Ibn Majah)
“We were standing in a place that was far from the place of standing. Ibn Mirba’ came to us and said: ‘I am the messenger of the Messenger of Allah (ﷺ) to you. He said: “Stay where you are today for today you are on the legacy of Ibrahim.’”
Grade:

Hadith #2749 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Ibn Majah)
“I heard ‘Abdur-Rahman bin Ya’mur Dili say: ‘I saw the Messenger of Allah (ﷺ) when he was standing at ‘Arafat, and some people from Najd came to him and said: “O Messenger of Allah, what is Hajj?” He said: “Hajj is ‘Arafah. Whoever comes before Fajr prayer on the night of Jam’, he has completed his Hajj. The days at Mina are three. ‘But whosoever hastens to leave in two days, there is no sin on him and whosoever stays on, there is no sin on him.’” Then he seated a man
Grade:

Hadith #2860 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Ibn Majah)
“The son of Adam does not do any deed on the Day of Sacrifice that is dearer to Allah than shedding blood. It will come on the Day of Resurrection with its horns and cloven hoofs and hair. Its blood is accepted by Allah before it reaches the ground. So be content when you do it.”
Grade:

Hadith #2867 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) slaughtered a cow on behalf of all his wives who had performed ‘Umrah, during the Farewell Pilgrimage.”
Grade:

Hadith #3080 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Ibn Majah)
“The family of Muhammad (ﷺ) never ate their fill of barley bread until he was taken (i.e. died).”
Grade:

Hadith #3425 - Sunan Ibn Majah - Ahmed bin Manay' أحمد بن منيع; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Ubaid'h bin Hameed عبيدة بن حميد (Sunan Ibn Majah)
“No person who mistreats his slave will enter Paradise.” They said: ” O Messenger of Allah, did you not tell us that this nation will have more slaves and orphans than any other nation?” He said: ” Yes, so be as kind to them as you are to your own children, and feed them with the same food that you eat.” They said: “What will benefit us in this world?” He said: “A horse that is kept ready for fighting in the cause of Allah, and your slave to take care of you, and if he perform
Grade:

Hadith #3426 - Sunan Ibn Majah - Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Ibn Majah)
“By the One in Whose Hand is my soul, you will not enter Paradise until you believe, and you will not believe until you love one another. Shall I not tell you of something which, if you do it, you will love one another? Spread (the greeting of) peace among yourselves.'”
Grade:

Hadith #3465 - Sunan Ibn Majah - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Uthman bin 'Abdur Rahman عثمان بن عبد الرحمن بن مسلم - الطرائفي (Sunan Ibn Majah)
“I met ‘Umar bin Khattab and he said: ‘Who are you?’ I said: ‘Masruq bin Adja’.’ ‘Umar said: ‘I heard the Messenger of Allah(ﷺ) saying,”Ajda’ is a devil.”
Grade:

Hadith #3630 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Ibn Majah)
“I heard the Messenger of Allah (ﷺ) say: ‘Prophecy is gone, but good dreams remain.’”
Grade:

Hadith #3698 - Sunan Ibn Majah - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Sulaiman bin Hayan al-Azdi سليمان بن حيان الأزدي (Sunan Ibn Majah)
“There are no two Muslims who confront one another with their swords, but both the killer and the slain will be in Hell.”
Grade:

Hadith #3758 - Sunan Ibn Majah - Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Ibn Majah)
“I said: ‘O Messenger of Allah, which people are most severely tested?’ He said: ‘The Prophets, then the next best and the next best. A person is tested according to his religious commitment. If he is steadfast in his religious commitment, he will be tested more severely, and if he is frail in his religious commitment, his test will be according to his commitment. Trials will continue to afflict a person until they leave him walking on the earth with no sin on him.’”
Grade:

Hadith #4070 - Sunan Ibn Majah - al-Hasan al-Basri الحسن البصري; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Yazid bin Zari' يزيد بن زريع (Sunan Ibn Majah)
“Kauthar is a river in Paradise whose banks are of gold and its bed is of rubies and pearls. Its soil is more fragrant than musk, its water is sweeter than honey and whiter than snow.”
Grade:

Hadith #4159 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Ibn Majah)
She said: “I heard The Messenger of Allah (ﷺ) say: ‘Whoever says anything about the Divine decree will be questioned about that on the Day of Resurrection, and whoever does not say anything about it will not be questioned about it.'” Another chain with similar wording.
Grade: